Parenting Style and Family Resilience with Children Congenital Rubella Syndrome - Sujani, Elfara Hajjar; Putro, Khamim Zarkasih (Department of Special Education, 2022)
This study aims to determine parenting patterns, family resilience with Congenital Rubella Syndrome, and the factors that influence family resilience. The method used is naturalistic with a case study approach. Research data was obtained by interview, observation, and documentation techniques. The data triangulation technique tested the validity of the data. The results of this study are: parents apply democratic parenting, parents can accept the child's condition, and the supporting factors are family and friends. Parents also seek information about their children's needs through seminars and others.